The Assessment of Human Erythroid Output in NOD/SCID Mice Reconstituted with Human Hematopoietic Stem Cells - Jun Hayakawa; Matthew M. Hsieh; D. Eric Anderson; Oswald Phang; Naoya Uchida; Kareem Washington; John F. Tisdale (Cell Transplantation, 2010)
The third-generation NOD/LtSz- scid / IL2R γ null (NOD/SCID IL2R γ null ) mouse represents a significantly improved xenograft model allowing high levels of human leukocyte engraftment over extended follow up. One remaining limitation of this mouse model, however, is the low level of circulating human erythrocytes. We established a practical ex vivo erythroid culture system of xenograft marrow progenitors to enrich for human erythroid progeny. At various time points after transplant, erythroid cells were easily assayed after 17 days of ex vivo culture of xenograft marrow, with nearly all nucleated cells of human origin and approximately 60% human GPA or CD71 positive. We then transplanted cord blood CD34 + cells marked with a lentiviral vector encoding green fluorescent protein (GFP). Three months later, ex vivo culture of xenograft marrow progenitors showed 41.3% of the cultured erythroid cells were positive for GFP and human CD71, and 56.2% were positive for GFP and human GPA, similar to that of circulating leukocytes at the same time point. Next, G-CSF mobilized peripheral blood CD34 + cells from a sickle cell trait subject were infused in this mouse model to determine if the hemoglobin pattern could be modeled. CD34 + cells from the sickle cell trait subject engrafted equally compared to CD34 + cells from normal subjects, establishing the sickle cell trait phenotype. Lastly, a comparison of adult-derived peripheral blood CD34 + cells and cord blood-derived CD34 + cells xenografted mice was made, and long term follow-up demonstrated a recapitulation of the fetal to adult hemoglobin switch. This approach should prove a useful tool for testing strategies for genetic manipulation of erythroid progeny and the study of hemoglobin switching.